Literary translation workshop: Social constructivist approach classroom activities - (:unkn) unknown (ELSEVIER SCIENCE BV, 2014)
This paper intends to present the literaiy translation workshop designed according to the guiding principles of the social constructivist approach, which are collaborative learning, scaffolding and professional self-concept. The significance of the literaty translation workshop is its contribution to the development of translation and translator competence through real life experience and collaborative construction of knowledge. Literary translation workshop ended in the publication of short stories translated by students in a literary magazine. (C) 2014 The Authors. Published by Elsevier Ltd.
Keywords: translator training; teaching literary translation; social constructivist approach; literary translation workshop; collaborative learning; authentic translation task; translation competence; translator competence